2017
DOI: 10.5935/2525-5711.20170007
|View full text |Cite
|
Sign up to set email alerts
|

Reemerging syphilis

Abstract: Abstract:Background: Syphilis cases have increasing worldwide recently, indicating a resurgence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…There have been reports of increasing cases of syphilis in recent years, from different parts of the world, mainly the USA, Canada, China, Russia, parts of Europe, Australia, and Brazil. [ 6 ] In the USA, the rate of primary and secondary syphilis decreased throughout the 1990s, reached an all-time low in 2000, and increased 11.1% in 2004–2005. [ 7 ] In Brazil, there was a significant increase between 2010 and 2016, with 230,000 new cases of the disease being reported.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports of increasing cases of syphilis in recent years, from different parts of the world, mainly the USA, Canada, China, Russia, parts of Europe, Australia, and Brazil. [ 6 ] In the USA, the rate of primary and secondary syphilis decreased throughout the 1990s, reached an all-time low in 2000, and increased 11.1% in 2004–2005. [ 7 ] In Brazil, there was a significant increase between 2010 and 2016, with 230,000 new cases of the disease being reported.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a small percentage of students reported knowledge about the differential diagnoses of oral manifestations of the disease. Indeed, studies have shown that the diagnosis of oral manifestations of syphilis represents a challenge for professionals because they have a variety of clinical appearances [12,13]. The fact that some characteristics may be similar to other conditions is of concern, and if diagnosis is not performed in the primary and secondary stages, the patient is exposed to the risk of complications related to the tertiary stage [12].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a small percentage of students reported knowledge about the differential diagnoses of oral manifestations of the disease. Indeed, studies have shown that the diagnosis of oral manifestations of syphilis represents a challenge for professionals because they have a variety of clinical appearances [23,24]. The fact that some characteristics may be similar to other conditions is of concern, and if diagnosis is not performed in the primary and secondary stages, the patient is exposed to the risk of complications related to the tertiary stage [23].…”
Section: Discussionmentioning
confidence: 99%